2020
DOI: 10.1088/1361-6560/ab6f98
|View full text |Cite
|
Sign up to set email alerts
|

A novel radiomic nomogram for predicting epidermal growth factor receptor mutation in peripheral lung adenocarcinoma

Abstract: To predict the epidermal growth factor receptor (EGFR) mutation status in patients with lung adenocarcinoma using quantitative radiomic biomarkers and semantic features. We analyzed the computed tomography (CT) images and medical record data of 104 patients with lung adenocarcinoma who underwent surgical excision and EGFR mutation detection from 2016 to 2018 at our center. CT radiomic and semantic features that reflect the tumors’ heterogeneity and phenotype were extracted from preoperative non-enhanced CT sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 27 publications
(23 reference statements)
0
38
2
Order By: Relevance
“…In total, 33 studies investigating radiomics and biological endpoints for lung lesions were identified. The imaging modalities employed were CT ( n = 22) [ 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ], PET/CT ( n = 8) [ 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 ], PET ( n = 2) [ 100 , 101 ] and MRI ( n = 1) [ 102 ]. One study investigated radiomics from metastases, while all other studies associated tissue biomarkers with radiomics of the primary tumor.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In total, 33 studies investigating radiomics and biological endpoints for lung lesions were identified. The imaging modalities employed were CT ( n = 22) [ 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ], PET/CT ( n = 8) [ 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 ], PET ( n = 2) [ 100 , 101 ] and MRI ( n = 1) [ 102 ]. One study investigated radiomics from metastases, while all other studies associated tissue biomarkers with radiomics of the primary tumor.…”
Section: Resultsmentioning
confidence: 99%
“…Almost half of the studies selected histological subtypes and used adenocarcinoma patients only ( n = 15), whereas the other half used a mix of histologies. Research has predominantly focused on EGFR ( n = 26) [ 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 92 , 93 , 94 , 95 , 96 , 97 , 100 , 101 , 102 ], followed by KRAS ( n = 5) [ 83 , 97 , 100 , 101 , 102 ], ALK ( n = 3) [ 87 , 98 , 102 ], PD-L1 ( n = 3) [ 88 , 89 , 99 ], Ki-67 ( n = 2) [ 90 , 91 ], and TP-53 ( n = 1) [ 84 ]. All studies showed a significant relationship between EGFR and radiomic features (AUC = 0.66–0.95).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are different treatment methods in mutated EGFR group and wild type EGFR group (18), so generally, their prognosis was studied separately. However, many previous studies have shown that radiomic has a high accuracy in distinguishing wild and mutated EGFR NSCLC patients (19,20), therefore, we combined two groups to increase the universality of the models. We also performed subgroup analysis which indicated that the radiomic signature own higher discrimination capacity for wild type EGFR group than mutated EGFR subgroup for all cut-off time points.…”
Section: Discussionmentioning
confidence: 99%